Carbapenem resistant Enterobacterales in the United Arab Emirates: a retrospective analysis from 2010 to 2021 - Jens Thomsen; Jens Thomsen; Najiba M. Abdulrazzaq; The UAE AMR Surveillance Consortium; Dean B. Everett; Dean B. Everett; Dean B. Everett; Godfred Antony Menezes; Abiola Senok; Abiola Senok; Carole Ayoub Moubareck (Frontiers Media S.A., 2023)
BackgroundCarbapenem-resistant Enterobacterales (CRE) are spreading in the United Arab Emirates (UAE) where their dissemination is facilitated by international travel, trade, and tourism. The objective of this study is to describe the longitudinal changes of CRE as reported by the national AMR surveillance system of the UAE.MethodsIn this study, we retrospectively describe CRE isolated from 317 surveillance sites, including 87 hospitals and 230 centers/clinics from 2010 to 2021. The associated clinical, demographic, and microbiological characteristics are presented by relying on the UAE national AMR surveillance program. Data was analyzed using WHONET microbiology laboratory database software (http://www.whonet.org).ResultsA total of 14,593 carbapenem resistant Enterobacterales were analyzed, of which 48.1% were carbapenem resistant Klebsiella pneumoniae (CRKp), 25.1% carbapenem resistant Escherichia coli (CREc), and 26.8% represented 72 other carbapenem resistant species. Carbapenem resistant strains were mostly associated with adults and isolated from urine samples (36.9% of CRKp and 66.6% of CREc) followed by respiratory samples (26.95% for CRKp) and soft tissue samples (19.5% for CRKp). Over the studied period carbapenem resistance rates remained high, especially in K. pneumoniae, and in 2021 were equivalent to 67.6% for imipenem, 76.2% for meropenem, and 91.6% for ertapenem. Nevertheless, there was a statistically significant decreasing trend for imipenem and meropenem resistance in Klebsiella species (p < 0.01) while the decrease in ertapenem resistance was non-significant. Concerning E. coli, there was a statistically significant decreasing trend for meropenem and imipenem resistance over the 12 years, while ertapenem resistance increased significantly with 83.8% of E. coli exhibiting ertapenem resistance in 2021. Resistance rates to ceftazidime and cefotaxime remained higher than 90% (in 2021) for CRKp and cefotaxime rates increased to 90.5% in 2021 for CREc. Starting 2014, resistance to colistin and tigecycline was observed in carbapenem resistant Enterobacterales. CRE were associated with a higher mortality (RR: 6.3), admission to ICU (RR 3.9), and increased length of stay (LOS; 10 excess inpatient days per CRE case).ConclusionThis study supports the need to monitor CRE in the UAE and draws attention to the significant increase of ertapenem resistance in E. coli. Future surveillance analysis should include a genetic description of carbapenem resistance to provide new strategies.